Interactive mockup to calculate arc length using integrals. Issue 1 (1st September 2022) - Velasco, Nancy; Karen, Chamorro; Morales, Marcia; Mendoza, Darío
Abstract: In the present work, a model of a Roman Arch is built and the Integral Calculus is applied to determine the Length of the Arch in Cartesian and Parametric coordinates, and the area in Polar coordinates. The objective is to create an enjoyable learning environment to the mathematics students. The educational model is made of wood and is made up of small blocks. Students must assemble the arch using two pieces of brackets and a clamp, without touching the blocks with their hands. An internal competition is carried out to determine the group of three people to do it in the shortest time. The activity creates an enjoyable environment to deal with these topics and makes student learning productive.